Rancang Bangun Prototype Sistem Monitoring Pemberian Pakan Ikan Otomatis di Keramba Jaring Apung Berbasis IoT - Rahmat Eka Putra; Ryan Fikri (Lembaga Yasin AlSys, 2025)
Floating net cage (KJA) fish farming in Lake Maninjau faces several challenges, particularly the inefficiency of manual feeding—which requires significant time and labor and often results in uneven distribution—as well as water quality issues caused by pollution and upwelling (tubo) phenomena, leading to mass fish mortality. This study aims to develop an Internet of Things (IoT)-based prototype to automate feeding and monitor water quality, thereby improving farming efficiency. The prototype was built using the ESP32 microcontroller, DS18B20 temperature sensor, pH sensor, HC-SR04 ultrasonic sensor, DS3231 RTC module, servo motor, buzzer, LED, and LCD display, following the waterfall development model. Sensor validation was performed using standard instruments such as thermometers and pH meters. The Blynk platform was used for remote monitoring and control via smartphone. The system successfully monitored water temperature within the range of 27–32°C, pH between 6–8.5, and feed levels (0–100%), with a deviation of ±0.01 for pH and 0.0°C for temperature. A total of 150 grams of feed was automatically dispensed at scheduled times (09:00 and 16:00 WIB), with notifications sent via Blynk. These findings demonstrate that the developed system effectively supports more efficient, adaptive, and environmentally responsive fish farming.